STUDI RUANG SINEMATIK KOMPLEK SUSTER-SUSTER ST. FRANSISKUS DI SEMARANG - Nadira Anandisya; Caecilia S. Wijayaputri (Riset Arsitektur (RISA), 2022)
Abstract - Cinema and Architecture are two art media that dependent on some human senses to give experience and define space compared of other art medium. These two media have been trying to show and convince film viewers or architecture users as a work of art. Both have quality value that will be higher if they can be as close to reality. However, architecture tend to use visual but lack of emotions. As a result, buildings left us as only a viewers without invite us to engaged. Therefore, from cinema to architecture, the thinking of thematic conditions of architecture can be brought together with conceptual, contextual, architectonic, and technical. Ave Maryam (2020) is a film that takes place in Semarang, and Kompleks Susteran St. Fransiskus is the main setting that interesting to studied. From each scene it can clearly describe space with a visual composition to convey a strong spatial experience. Departing from an approach to cinema that is parallel to architecture so that the audience can experience spaces outside the formal architectural experience. The purpose of this study is to identify cinematic themes that can be discussed and reconstruct the cinematic space as a search for understanding the potential and meaning of cinematic in Kompleks Kesusteran St. Fransiskus based on the film Ave Maryam (2020). By using a qualitative descriptive method, from data that achieved by literature studies and film observations. It can be concluded that the existing approaches to architecture and cinema from Ave Maryam (2020) can be interpreted to build a concept that achieves the beauty and experience experienced in architecture such as watching the film. Key Words: cinematic, architecture and film, cinematic approach, Ave Maryam, Komplek Kesusteran St. Fransiskus, Semarang.